Enhancing The Digital Ecosystem and Empowering Community Businesses In Pedurungan Lor Through The Productive Waqf-Based SIWAP - Jayanto, Prabowo Yudo; Kuswantoro, Agung; Mustofa , Ubaedul (Universitas Negeri Semarang, 2024)
Based on the evaluation of the situation, there are several main problems that require priority handling in the effort to empower the novice community. These problems include limitations in capital, lack of integrated information, promotion, sales, and financial management systems, and lack of knowledge of the potential and challenges faced by Pedurungan Lor Village, Pedurungan District, Semarang. To overcome these challenges, the main objective of the startup community empowerment is to initiate a Productive waqf-based crowdfunding called SIWAP, with the aim of providing access to capital to goat farming groups, tourism village management, and product development from creative business groups in Pedurungan Lor Village. SIWAP will function as a tourism marketplace that not only provides a platform for promotion and sales, but also offers integrated solutions for financial management. The goals of the program include increased capital, turnover, and net profit of the business groups, publication through electronic media and national journals, and video documentation of activities. Additional expected outcomes include the establishment of SIWAP crowdfunding and intellectual property rights protection. The activity plan will include a survey of partner locations, design and creation of the SIWAP crowdfunding platform, training for system users, technology implementation, and regular mentoring and monitoring of the use of the SIWAP system by business groups in Pedurungan Lor Village, Pedurungan District, Semarang.